Retinoic acid inhibits calmodulin binding to human erythrocyte membranes and reduces membrane Ca2(+)-adenosine triphosphatase activity. - Davis, F B (1990)
Ca2(+)-ATPase activity in human red cell membranes is dependent on the presence of calmodulin. All trans-retinoic acid inhibited human red cell membrane Ca2(+)-ATPase activity in vitro in a concentration-dependent manner (10(-8) to 10(-4) M). In contrast, retinol, retinal, 13-cis-retinoic acid and the benzene ring analogue of retinoic acid did not alter enzyme activity. Purified calmodulin (up to 500 ng/ml, 3 X 10(-8) M) added to red cell membranes, in the presence of inhibitory concentrations of retinoic acid, only partially restored Ca2(+)-ATPase activity. 125I-Calmodulin bound to red cell membranes was displaced by unlabeled retinoic acid (50% reduction at 10(-8) M retinoic acid), as effectively as by unlabeled calmodulin. Another calmodulin-stimulable enzyme, bovine brain cyclic nucleotide phosphodiesterase, was unaffected by retinoic acid. 8-Anilino-1-naphthalene sulfonic acid bound to calmodulin, studied spectrofluorometrically, was not displaced by retinoic acid. Thus, retinoic acid inhibits calmodulin binding to red cell membranes, reducing calmodulin-stimulable Ca2(+)-ATPase activity. Retinoic acid does not directly interact with calmodulin, but rather exerts its effect by interfering with calmodulin access to the membrane enzyme. These effects occur at physiological concentrations of the retinoid.